A three-component hydrograph separation based on geochemical tracers in a tropical mountainous headwater catchment in northern Thailand - C. Hugenschmidt (2018)
Land-use change in the mountainous parts of northern Thailand is reflected by an increased application of agrochemicals, which may be lost to surface and groundwater. The close relation between flow paths and contaminant transport within hydrological systems requires recognizing and understanding the dominant hydrological processes. To date, the vast majority of studies on runoff generation have been conducted in temperate regions. Tropical regions suffer from a general lack of data, and little is known about runoff generation processes. To fill this knowledge gap, a three-component hydrograph separation based on geochemical tracers was carried out in a steep, remote and monsoondominated study site (7 km2) in northern Thailand. Silica and electrical conductivity (EC) were identified as useful tracers and were applied to calculate the fractions of groundwater (similar to pre-event water), shallow subsurface flow and surface runoff on stormflow. K + was a useful indicator for surface runoff dynamics, and Ca2 + provided insights into groundwater behaviour. Nevertheless, neither measure was applicable for the quantification of runoff components. Cl? and further parameters (e.g. Na + , K + , and Mg2 + ) were also not helpful for flow path identification, nor were their concentrations distinguishable among the components. Groundwater contributed the largest fractions to stormflow (62-80 %) throughout all events, followed by shallow subsurface flow (17-36 %) and surface runoff (2-13 %). Our results provide important insights into the dynamics of the runoff processes in the study area and may be used to assess the transport pattern of contaminants (i.e. agrochemicals) here. © Author(s) 2014. CC Attribution 3.0 License.